Impact of obesity and type 2 diabetes on health-related quality of life in the general population in England. - Gough, S; Kragh, N; Ploug, U; Hammer, M (2009)
BACKGROUND: Weight gain can contribute towards the development of type 2 diabetes (T2D), and some treatments for T2D can lead to weight gain. The aim of this study was to determine whether having T2D and also being obese had a greater or lesser impact on health-related quality of life (HRQoL) than having either of the two conditions alone. METHODS: The 2003 dataset of the Health Survey for England (HSE) was analyzed using multiple regression analyses to examine the influence of obesity and T2D on HRQoL, and to determine whether there was any interaction between these two disutilities. RESULTS: T2D reduced HRQoL by 0.029 points, and obesity reduced HRQoL by 0.027 points. There was no significant interaction effect between T2D and obesity, suggesting that the effect of having both T2D and being obese is simply additive and results in a reduction in HRQoL of 0.056. CONCLUSIONS: Based on analysis of HSE 2003 data, people with either T2D or obesity experience significant reduction in HRQoL and people with both conditions have a reduction in HRQoL equal to the sum of the two independent effects. The effect of obesity on HRQoL in people with T2D should be considered when selecting a therapy.